2z-4=6

Simple and best practice solution for 2z-4=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2z-4=6 equation:


Simplifying
2z + -4 = 6

Reorder the terms:
-4 + 2z = 6

Solving
-4 + 2z = 6

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 2z = 6 + 4

Combine like terms: -4 + 4 = 0
0 + 2z = 6 + 4
2z = 6 + 4

Combine like terms: 6 + 4 = 10
2z = 10

Divide each side by '2'.
z = 5

Simplifying
z = 5

See similar equations:

| 0.04x+0.13(10000-x)= | | 8u=-1/3 | | 2(2x)+2(4)=40 | | 7u-2=4u+10 | | 2(2x)+2(2)=40 | | w+3.9=7.21 | | 130=95 | | -7+1=y-3y | | -24=5r+-8 | | 5(x+5)^1/2 | | x-1/2-7=x-5/3 | | (x+5)^5/2 | | (2/5d)-(1/9d) | | (6x+30)^3/2 | | 4x+5+3x+8=180 | | 21=-7/3w | | V+2v=15 | | -3(2x-2y)=-24 | | 1/3x+1/5y=-2/3 | | Q-17=17 | | 1/3+1/3(2x-15)=31/2 | | k^2=-3 | | 2(3x+y)=14 | | w-7/3=5/3 | | -4x(x-7)=40 | | x-7/2-1=x-5/3 | | 5y+8x=6(3.14) | | 6.3=b-1.5 | | 2y(3y-4y+6)=4 | | 1/2-45x=225 | | -18=r-12 | | 5x/4-8=x/2+7 |

Equations solver categories